Thermodynamic Properties of a Gas–Liquid–Solid System during the CO2 Geological Storage and Utilization Process: A Review - Meiheriayi Mutailipu; Qingnan Xue; Tao Li; Yande Yang; Fusheng Xue (Energies, 2023)
Emission reduction in the main greenhouse gas, CO2, can be achieved efficiently via CO2 geological storage and utilization (CCUS) methods such as the CO2 enhanced oil/water/gas recovery technique, which is considered to be an important strategic technology for the low-carbon development of China’s coal-based energy system. During the CCUS, the thermodynamic properties of the CO2–water–rock system, such as the interfacial tension (IFT) and wettability of the caprock, determine the injectability, sealing capacity, and safety of this scheme. Thus, researchers have been conducting laboratory experiments and modeling work on the interfacial tension between CO2 and the water/brine, wettability of caprocks, the solubility of gas–liquid binary systems, and the pH of CO2-saturated brine under reservoir temperature and pressure conditions. In this study, the literature related to the thermodynamic properties of the CO2–water–rock system is reviewed, and the main findings of previous studies are listed and discussed thoroughly. It is concluded that limited research is available on the pH of gas-saturated aqueous solutions under CO2 saline aquifer storage conditions, and less emphasis has been given to the wettability of the CO2–water/brine–rock system. Thus, further laboratory and modeling research on the wettability alternations of caprock in terms of molecular dynamics is required to simulate this phenomenon at the molecular level. Moreover, simplified IFT and solubility prediction models with thermodynamic significance and high integrity need to be developed. Furthermore, interaction mechanisms coupling with multi-factors associated with the gas–liquid–solid interface properties and the dissolution and acidification process need to be explored in future work.